Measurement of coverage, compliance and determinants of uptake in a publicly funded rotavirus vaccination programme: a retrospective cohort study - Lawrence W Svenson; Ellen Rafferty; Xiaoyan Guo; Bruce McDonald; Shannon Elizabeth MacDonald (BMJ Open, 2019)
Objectives In June 2015, Alberta, Canada instituted a universal publicly funded rotavirus vaccination programme (Rotarix, RV1), with vaccine doses scheduled for 2 and 4 months of age. Vaccination was restricted so that infants were only allowed to receive first dose between 6 and 20 weeks of age, and second dose before eight calendar months of age. We assessed the coverage and schedule non-compliance of rotavirus vaccination for babies born between June 2015 and August 2016, that is, since the inception of the publicly funded rotavirus vaccination programme, and determined factors associated with rotavirus vaccine uptake.Design Retrospective cohort study using linked administrative health data.Setting Alberta, Canada.Participants Cohort of 66 689 children.Primary and secondary outcome measures (1) First and second dose rotavirus vaccination coverage, (2) percent of children non-compliant with recommended vaccine schedule and (3) adjusted ORs for factors associated with vaccination status.Results For the 66 689 children included in the study, coverage levels for one-dose and two-dose rotavirus vaccination were 87% and 83%, respectively. In comparison, two-dose diphtheria-tetanus-pertussis-polio-Haemophilus influenzae type b vaccine coverage was 92%, despite having the same dosing schedule. Schedule non-compliance during the publicly funded programme was very low. We observed socioeconomic disparities in the uptake of the vaccine, with income, location of residence and number of children in the household all contributing to the odds of a child being vaccinated with rotavirus.Conclusions Compliance to the recommended rotavirus schedule was very high, suggesting that even with the restrictive rotavirus vaccine schedule, the vaccine can be delivered on-time. However, rotavirus vaccine coverage remained lower than DTaP, a similarly scheduled childhood vaccination. We also observed socioeconomic disparities in vaccine uptake. These findings raise concerns about rotavirus protection in the groups at highest risk for gastrointestinal illness, including low-income and rural populations.